Cognitive flexibility as a protective factor for empathy - Cai, Zhiwei; Qi, Bing (Frontiers in Psychology, 2023)
Although cognitive flexibility has always been considered essential to empathy, the relevant findings have been inconsistent. Inconsistent results may be because cognitive flexibility is a multi-level structure, while empathy is also a multilayer structure, and there are differences in how researchers define and measure cognitive flexibility. Therefore, the study explores the relationship between cognitive flexibility and empathy from a multi-dimensional perspective. This study involved 105 China students aged between 18 and 22 (M age = 20.26, SD = 2.00) who completed the Cognitive Flexibility Scale (cognitive flexibility trait, cognitive flexibility at the individual level), perspective-switching flexibility task (perspective-switching flexibility, cognitive flexibility at the cognitive level), the Interpersonal Reactivity Index scale (IRI, traits empathy), Multi-dimensional Empathy Test (state empathy), 2-back task (inhibitory control), and Stroop task (working memory). After controlling for additional variables, the results showed that: (1) Cognitive flexibility traits negatively predicted trait cognitive (IRI-PT) and affective empathy (IRI-EC). (2) The Other/Self perspective-switching flexibility negatively predicted the affective component of state empathy. (3) Cognitive flexibility traits and Other/Self perspective-switching flexibility negatively predicted empathy even after controlling for one of these. The study’s results suggested that cognitive flexibility negatively predicts empathy and is a protective factor for reducing the cost of empathy and promoting emotion regulation.